If , then in which interval is the function decreasing?
Details:
represents sawtooth function . That is,
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First of all, f ( x ) is decreasing iff f ′ ( x ) < 0 , so, to answer the question, it suffices to find when f ′ ( x ) < 0 .
The sawtooth function is a little hard to analyze, but I find it helpful to let x = n + ϵ , where n is an integer and 0 ≤ ϵ < 1 . This allows us to do more, because ⌊ n + ϵ ⌋ = n + ⌊ ϵ ⌋ = n + 0 = n (you are allowed to pull integers out of the floor function, and ϵ is between 0 and 1, so it will be sent to 0).
With our new method, we can tackle the sawtooth function. First, input x = n + ϵ :
{ n + ϵ } = n + ϵ − ⌊ n + ϵ ⌋ = n + ϵ − n = ϵ
So f ′ ( n + ϵ ) = ∣ n + ϵ ∣ − { n + ϵ } = ∣ n + ϵ ∣ − ϵ
This is much easier to work with. Let's try looking at it in different cases. We'll start with n ≥ 0 :
Because we also chose ϵ to be nonnegative, n + ϵ is nonnegative, so ∣ n + ϵ ∣ = n + ϵ . Let's try and use that.
First, we're looking for f ′ ( x ) < 0 ⇒ ∣ n + ϵ ∣ − ϵ < 0 ⇒ ∣ n + ϵ ∣ < ϵ
Let's plug in our absolute value:
∣ n + ϵ ∣ = n + ϵ < ϵ ⇒ n < 0
But we said n ≥ 0 ! Therefore, the interval we're looking for doesn't contain any x = n + ϵ such that n ≥ 0 .
Real quickly, take a step back: what values did we just eliminate? Well, we just eliminated n ≥ 0 and we know ϵ ≥ 0 , so we eliminated all values where n + ϵ ≥ 0 , meaning that our interval must only contain negative values.
[note: out of all the options listed, only one meets this criterion, so this would be enough to answer this multiple-choice question]
So, we just showed that n ≱ 0 ⇒ n < 0
Let − m = n , so m > 0 . Now, n + ϵ = ( − m ) + ϵ = ϵ − m which must be negative, so ∣ ϵ − m ∣ = m − ϵ Like before, we will use this.
f ′ ( x ) < 0 ⇒ ∣ n + ϵ ∣ − ϵ = ∣ ϵ − m ∣ − ϵ = m − ϵ − ϵ = m − 2 ϵ < 0 ⇒ m < 2 ϵ
We know that 0 ≤ ϵ < 1 , so 0 ≤ 2 ϵ < 2 Therefore, m < 2 ϵ implies m < 2 Remember that m = − n , so − n < 2 ⇒ n > − 2 This means that n is an integer between − 2 and 0 , leaving only n = − 1
Before we saw that m < 2 ϵ Because m = − n = − ( − 1 ) = 1 , we know that 1 < 2 ϵ ⇒ 2 1 < ϵ
(note: because we are talking about − 1 + ϵ , larger values for ϵ correspond to smaller values after the decimal point)
So, 2 1 < ϵ < 1 , meaning that f ( x ) is decreasing on the open interval ( − 1 + 2 1 , − 1 + 1 ) = ( − 2 1 , 0 )